A clinical profile of revision cochlear implant surgery: MERF experience. (4th March 2021) - Rayamajhi, Pabina; Kurkure, Rahul; Castellino, Ashish; Kumar, Santhosh; HA, Manjunath; Nandhan, Raghu; Kameswaran, Mohan
Abstract : Objective: To study the prevalence of revision cochlear implant study in a tertiary care referral center. To assess the various indications and surgical outcomes of revision cochlear implant surgery. Methods: A retrospective chart review of revision cochlear implant surgery done from June 1997 to December 2019. All the surgeries that were done in children of 12 years and below were included. The revision surgeries were either with or without explantation and reimplantation. The causes included were device failures, electrode extrusion/malposition, magnet migration, persistent foreign body reaction, facial twitching, wound infection, and cholesteatoma. Results: A total of 1636 pediatric cochlear implantation surgery were performed during the study period of 22 years. There were 94 (5.7%) revision surgeries done for various indications during this period. Out of them, 67 patients (71.3%) had device failure thus being the commonest indication for revision surgery, followed by infection in 12.8% of the total patients. Among the total revision, 81 (86.2%) patients had explantation and reimplantation of the new device. Conclusion: Indications of revision cochlear implant surgery are manifold that can be either device-related or patient-related. Revision surgery needs a highly skilled and experienced team of surgeons, audiologists, and habilitationists for achieving optimal results.